Pulsar da Medusa: um experimento de criação cênica e estudo da expressividade do corpo-voz a partir dos fatores do movimento de Rudolf Laban - Silva, Rosana Figueiredo da [UNESP] (2015)
The present research aims to reflect a scenic experiment creation: the creative process of the play Pulsar da Medusa, which was directed by me. It's about an approach of dance theatre based in the expressive study of body vocal, using factors from Rudolph Laban: space, time, weight and fluency. The approach of this scenic experiment occur by my point of view as a director. Here I broach about my labour with the apprentice actor and apprentice actress from the play. This kind of direction purpose a preparative labour for the representation/acting, through body and vocal exercises, with orientation of the creative labour. It's a direction-bearings labour. The research counted with the collaboration from two-apprentice actress and one apprentice actor, who had, with me, the role of scenic creators. The fundamental intention of the direction was the instruction of the actress and actor, for this reason aimed more than aesthetics results. The process was seem especially as a way of learning at the expressivity field of body vocal and scenic composition. The play was elaborate as an exercise of creation, inspired on the book Água-viva, by Clarice Lispector. In addition, is available questionnaires, which was answered by the apprentice actress and the apprentice actor, who collaborated with the research. These questionnaires help us to verify if the exercises were important for the body and vocal development. Beyond this, it contains some videos, which show fragments from the presentation and from the rehearsals. As I approach aspects as my role of director and guiding, as the role of actor/actress, this research may to contribute with artists who play different roles inside of the creative process. Additionally, it serves as a reference to teachers and researchers in the field of theatre and dance creation.